Sulfide solid electrolyte based on ionic liquid electrowetting modification and application thereof

By electrowetting the modified sulfide solid electrolyte through ionic liquid, the problem of poor contact between the sulfide solid electrolyte and the electrode interface is solved, and a pressure-free all-solid lithium metal battery is realized, which significantly improves the cycle stability and life of the battery.

CN119627199AInactive Publication Date: 2025-03-14SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1

Patent Information

Application Number
CN202510147323.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The interface contact between the sulfide solid electrolyte and the electrode is poor, resulting in an increase in ion transport impedance and a decrease in cycling performance. The existing improvement methods have problems such as complex preparation processes, high cost and difficulty in mass production.

Method used

The modified sulfide solid electrolyte is used to electrowet the application of DC signals to significantly reduce the interface impedance and improve the power density and rate performance of the battery.

Benefits of technology

A pressure-free assembly of all-solid lithium metal batteries is achieved. The battery can still maintain a capacity of more than 90% after 500 cycles, and the cycle life is increased by about 1,000%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627199A_ABST
    Figure CN119627199A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfide solid electrolyte based on ionic liquid electrowetting modification and application thereof. The preparation method of the electrolyte comprises the following steps: preparing a sulfide electrolyte into an electrolyte sheet, and coating the surface of the electrolyte sheet with an ionic liquid to form an ionic liquid film, thereby obtaining the electrolyte sheet containing the ionic liquid film; and placing the sulfide solid electrolyte between electrode plates which are arranged in parallel to assemble a parallel-plate capacitor, and applying a direct-current signal to carry out electrowetting treatment, thereby obtaining the sulfide solid electrolyte based on ionic liquid electrowetting. The specific ionic liquid is introduced into the interface of the sulfide solid electrolyte and the negative electrode for electrowetting treatment, so that the interface contact angle is effectively reduced, the interface wettability is improved, the interface impedance is reduced, the electrochemical performance of the all-solid-state battery is improved, and the cycle life of the all-solid-state battery is prolonged. The method particularly focuses on the use of imidazole and pyridine ionic liquids, and selects the appropriate ionic liquid for the lithium metal negative electrode material to realize the optimal interface modification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state lithium batteries, and relates to a sulfide solid electrolyte based on ionic liquid electrowetting modification and its application, especially in an all-solid-state battery. Background Art

[0002] All-solid-state batteries are considered promising candidates for the next generation of energy storage technology due to their potential high energy density and safety. Among them, sulfide solid electrolytes have attracted extensive attention due to their advantages such as high ionic conductivity, good mechanical ductility and easy processing.

[0003] However, poor interfacial contact between sulfide SSEs and electrodes remains one of the key issues restricting their performance. Poor interfacial contact can lead to increased ion transfer impedance and decreased cycle performance. In order to improve solid-solid interfacial contact, researchers have proposed a variety of strategies, including interface modification, thin film preparation, and in-situ curing. Although these methods have achieved some results to a certain extent, they often have problems such as complex preparation process, high cost, and difficulty in large-scale production, which limits their practical application value.

[0004] To this end, the present invention introduces an electrowetting step, that is, assembling a parallel plate capacitor and applying a DC signal. By applying an electric field, the wetting effect of the ionic liquid on the interface can be significantly enhanced, which cannot be achieved by a simple coating method. The present invention proposes a concept of applying to a pressure-free all-solid-state lithium metal battery. The prepared sulfide solid electrolyte has a lower interface impedance: electrowetting can more effectively reduce the interface impedance and improve the power density and rate performance of the battery; higher energy density: pressure-free assembly can reduce the weight of the battery, thereby improving the energy density; simpler production process: pressure-free assembly can simplify the production process and reduce production costs. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a sulfide solid electrolyte modified by ionic liquid electrowetting and its application to improve the interface contact and improve the performance of all-solid-state batteries. It aims to overcome the practical application limitations of the traditional method of improving the interface contact by applying pressure. Ionic liquids show great potential in improving the interface contact of solid-state batteries. Specifically, ionic liquids can improve the contact angle problem between sulfide electrolytes and negative electrodes through the following mechanisms. On the one hand, under the application of an electric field, ionic liquids can significantly reduce the solid-solid interface contact angle and improve wettability, thereby promoting close contact between sulfide electrolytes and negative electrodes and reducing interface voids. On the other hand, ionic liquids can penetrate into the pores and irregular surfaces of sulfide electrolytes and negative electrodes to form a more uniform interface and reduce interface impedance. On the other hand, ionic liquids can react with sulfide electrolytes or negative electrodes to form an interface layer with good ionic conductivity, further improving ion transport. It can achieve the operation of all-solid-state lithium metal batteries without pressure.

[0006] The present invention can overcome the traditional method of improving interface contact by applying pressure, thereby realizing a pressure-free all-solid-state lithium metal battery. The ionic liquid electrowetting modified sulfide solid electrolyte of the present invention is applied to an all-solid-state lithium metal battery and can still maintain more than 90% of the capacity after 500 cycles, and the cycle life is increased by about 1000%.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: <First aspect> The present invention provides a sulfide solid electrolyte based on ionic liquid electrowetting modification, which is prepared by the following steps: S1, preparing a sulfide electrolyte into a flat electrolyte sheet, and then coating an ionic liquid on the surface of the electrolyte sheet to form an ionic liquid film, thereby obtaining an electrolyte sheet containing an ionic liquid film; S2. Placing the electrolyte sheet containing the ionic liquid film between parallel electrode plates to assemble into a parallel plate capacitor, applying a DC signal for electrowetting treatment, and obtaining a sulfide solid electrolyte modified by ionic liquid electrowetting.

[0008] As an embodiment of the present invention, in step S1, the sulfide electrolyte includes Li6PS5Cl, Li3PS4, Li 10 GeP2S 12 , Li6PS5Br, Li6PS5I.

[0009] As an embodiment of the present invention, in step S1, the particle size of the sulfide electrolyte raw material used is 1-8 μm. The particle size is controlled to obtain a dense electrolyte sheet. Too large a particle size will result in a high porosity of the sheet after pressing, affecting the ionic conductivity; too small a particle size will cause powder agglomeration and make it difficult to press uniformly.

[0010] As an embodiment of the present invention, in step S1, the preparation process of the electrolyte sheet is a cold pressing or hot pressing process. Cold pressing parameters: the pressure is usually in the range of 300MPa to 500MPa, and the holding time is usually between 10 minutes and 60 minutes. Hot pressing parameters: the temperature is usually between 100-200°C and the heating rate and cooling rate are controlled to be less than or equal to 1°C per minute, the pressure is usually in the range of 300MPa to 500MPa, and the holding time is usually between 2 hours and 6 hours. The present invention prepares the electrolyte into a flat sheet to avoid obvious defects on the surface.

[0011] As an embodiment of the present invention, the electrolyte sheet is prepared by a cold pressing process, the cold pressing pressure is 400 MPa, and the pressure is maintained for 30 minutes.

[0012] As an embodiment of the present invention, in step S1, the ionic liquid is one or more of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) and 1-butyl-1-methylpyrrolidino hexafluorophosphate (BMPPF).

[0013] Different ionic liquids have different physical and chemical properties (such as viscosity, surface tension, electrochemical window, etc.), which can improve different interface problems in a targeted manner. At the same time, different ionic liquids may have different degrees of contact angle change under the action of an electric field. By screening different ionic liquids, this application can find materials suitable for the surface of electrolyte sheets with better electrowetting properties, thereby more effectively reducing interfacial impedance. These specific ionic liquids may undergo interfacial chemical reactions with solid electrolytes or negative electrodes to form an interfacial layer with good ionic conductivity, further improving ion transport.

[0014] This application provides a variety of ionic liquids, which can be selected according to the specific solid electrolyte and negative electrode material to achieve the best matching effect. For example: the argyrodite electrolyte (Li6PS5X, X = Cl, Br, I) corresponds to 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF), which has a good effect; Li 10 GeP2S 12 The corresponding ionic liquid is 1-butyl-1-methylpyrrolidino hexafluorophosphate (BMPPF), which has a better effect.

[0015] The selection of ionic liquids must also meet the needs of electrolytes. The present invention is to modify the surface of sulfide electrolytes (extremely sensitive to water and air, and prone to decomposition reactions). For example, 1-butyl-2,3-dimethylimidazolium tetrafluoroborate ionic liquids may be used for other electrolytes, such as oxide electrolytes, but are not suitable for the sulfide electrolytes of the present invention. This is because tetrafluoroborate is relatively poor in hydrolysis stability and easily reacts with water to generate substances such as HF and boric acid. Hydrolysis may occur even in the presence of trace water. Sulfide electrolytes are very sensitive to water, and even if there is a trace amount of water in the ionic liquid, it may cause the decomposition of sulfide electrolytes. Compared with tetrafluoroborate, hexafluorophosphate has much better hydrolysis stability, is relatively stable in anhydrous environments, and is not prone to hydrolysis. This reduces the risk of side reactions with sulfide electrolytes. Therefore, the BMIMPF and BMPPF of the present invention have higher ionic conductivity and a wider electrochemical window, and are more suitable as electrolytes or interface modifiers for electrochemical devices.

[0016] As an embodiment of the present invention, in step S1, the ionic liquid is diluted before coating so that the viscosity of the ionic liquid is not higher than 30 mPa·s; the viscosity is preferably 0.3-5 mPa·s. If the viscosity of the ionic liquid is high (>30mPa·s), it needs to be diluted. Since the present invention requires the preparation of very thin nano-scale films, a lower viscosity is required. Generally speaking, if the viscosity of the ionic liquid at room temperature (25°C) exceeds 30 mPa·s, it usually needs to be diluted. In a specific embodiment of the present invention, in order to better control the uniformity and thickness of the film and optimize the electrowetting effect, the ionic liquid used is diluted. The solvent used for dilution includes one or more of acetonitrile and dichloromethane. The present invention dilutes the ionic liquid in a dry organic solvent, such as acetonitrile, dichloromethane, etc., for easy coating. Note that the choice of solvent should be compatible with the sulfide electrolyte and the ionic liquid and easy to volatilize.

[0017] As an embodiment of the present invention, in step S1, the thickness of the ionic liquid film formed is 50 nm-20 μm, preferably 50 nm-10 μm.

[0018] The thickness of the ionic liquid film has a significant impact on the performance of all-solid-state lithium metal batteries. If the thickness of the ionic liquid film is too low, a continuous wetting layer cannot be formed at the solid-solid interface. This means that the contact area at the interface is still limited, and the gaps and holes between the solid-solid interface still exist, resulting in poor wetting. The core of electrowetting is to reduce the contact angle and promote the spreading of droplets on the solid surface. If the thickness of the ionic liquid film is not enough, it may only slightly reduce the contact angle, unable to achieve the ideal wetting effect, and the interface impedance is difficult to effectively reduce. An ionic liquid film that is too thick may cause excessive interface viscosity, hindering the transmission of ions and increasing the interface impedance.

[0019] As an embodiment of the present invention, in step S1, the coating method is preferably spin coating. Spin coating parameters: spin coating at a rotation speed of 400-600 rpm for 55-65 seconds, and then continue to spin coating at a rotation speed of 1000-5000 rpm (preferably 1000-3000 rpm) for 25-35 seconds. Preferably, spin coating is performed at a rotation speed of 500 rpm for 60 seconds, and then spin coating is continued at a rotation speed of 1000-3000 rpm for 30 seconds. The present invention uses a spin coater to rotate at a high speed so that the liquid is evenly distributed on the surface of the electrolyte sheet to form a thin film, and the thickness of the film can be adjusted by controlling the spin coating speed and time.

[0020] As an embodiment of the present invention, in step S1, the electrolyte sheet containing the ionic liquid film is further placed in a protective atmosphere (Ar gas) for drying. Before use, the sheet is dried overnight in a glove box with an Ar gas atmosphere to allow the solvent to evaporate naturally and remove the adsorbed moisture.

[0021] As an embodiment of the present invention, in step S2, the voltage of the DC signal is 1-10V, and the time of the electrowetting treatment is 15-60 minutes. If the voltage is too low (lower than 1V), the electric field strength is insufficient to effectively change the wettability of the ionic liquid on the electrolyte surface, resulting in an insignificant electrowetting effect, limited improvement in interface contact, and failure to improve battery performance. If the voltage is too high (higher than 10V), the ionic liquid may undergo electrochemical decomposition at a higher voltage, affecting the electrowetting effect and causing a decrease in battery performance.

[0022] The electrowetting treatment of the present invention refers to the phenomenon of changing the contact angle between the solid surface and the liquid by applying an electric field. In the present invention, applying a DC signal will form an electric field at the interface between the solid electrolyte and the negative electrode, which can significantly reduce the contact angle between the ionic liquid and the solid electrolyte and the negative electrode, so that it can better wet the interface and fill the pores, thereby significantly reducing the interface impedance.

[0023] As an embodiment of the present invention, in step S2, the parallel plate capacitor is assembled by placing an electrolyte sheet containing an ionic liquid film on a second electrode plate (so that the ionic liquid film faces the second electrode plate), the ionic liquid film is in contact with the second electrode plate, and then an insulating spacer is placed on the electrolyte sheet, the first electrode plate is placed parallel to the insulating spacer, and finally a power supply or a signal generator is connected to the first and second electrode plates of the capacitor, and a DC signal (1-10V) is applied. The insulating spacer is used to control the distance between the first and second electrode plates to ensure good contact between the electrolyte sheet and the first and second electrode plates. The insulating spacer is located between the electrolyte sheet and the second electrode plate and does not cover the ionic liquid film area.

[0024] As an embodiment of the present invention, in step S2, when a DC signal is applied, the second electrode plate is connected to the negative electrode, and the first electrode plate is connected to the positive electrode ( Figure 4 ). The electrode plate disposed on one side of the electrolyte sheet coated with the ionic liquid film is connected to the negative electrode, and the electrode plate on the other side is connected to the positive electrode.

[0025] As an embodiment of the present invention, the operations of steps S1 and S2 are performed in a glove box or a dry environment. Since the sulfide electrolyte is sensitive to air and moisture, all operations are preferably performed in a glove box or a dry environment.

[0026] <Second Aspect> The present invention also provides an application of the sulfide solid electrolyte modified by ionic liquid electrowetting in an all-solid-state lithium metal secondary battery.

[0027] The present invention also provides an all-solid-state lithium metal secondary battery, comprising a negative electrode, a positive electrode and the above-mentioned modified sulfide solid electrolyte.

[0028] The negative electrode includes a lithium metal negative electrode or a metal lithium composite negative electrode.

[0029] The positive electrode includes one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide.

[0030] The present invention realizes pressure-free assembly through electrowetting treatment and has higher cycle stability. Pressure-free assembly: Traditional solid-state battery assembly requires the application of greater pressure to ensure interface contact, while the present application can significantly improve interface contact through electrowetting, thereby making it possible to achieve pressure-free assembly and simplify the production process. Higher cycle stability: The more stable interface formed by electrowetting may inhibit the growth of lithium dendrites and the occurrence of interface side reactions, thereby increasing the cycle life of the battery.

[0031] The preferred ionic liquids of the present invention are 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) and 1-butyl-1-methylpyrrolidium hexafluorophosphate (BMPPF). These ionic liquids have high ionic conductivity, which ensures good ion transmission at the interface; wide electrochemical window, which adapts to the working voltage range of the battery; good electrochemical stability, which is not prone to decomposition or side reactions; and suitable viscosity and surface tension, which are conducive to the conduction of electrowetting.

[0032] Compared with the all-solid-state lithium metal battery in the prior art, the beneficial effects of the present invention are: (1) One of the biggest challenges facing traditional all-solid-state batteries is the poor interface contact between the solid electrolyte and the electrode. Due to the lack of good physical contact between solid materials, there are a large number of pores and voids at the interface, which leads to obstructed ion transport and high interface impedance. In order to improve the interface contact, commonly used methods include applying external pressure, hot pressing, interface modification (such as coating an intermediate layer), etc., but these methods have certain limitations, such as the difficulty in evenly distributing pressure and the complex preparation process of the intermediate layer. The present invention introduces ionic liquids and utilizes their good wettability and electrowetting effect to effectively fill the gaps at the interface, increase the effective contact area between the solid-solid interface, and thus significantly reduce the interface impedance. Ionic liquids can penetrate into the micropores and irregular surfaces of sulfide electrolytes and electrodes to form a more uniform and tighter interface.

[0033] (2) The high interface impedance of the prior art directly leads to low ion transfer efficiency, which affects the rate performance and energy density of the battery. The ionic liquid of the present invention also has a certain ionic conductivity and can serve as a channel for ion transfer, further improving the ion transfer efficiency at the interface. The improved interface contact and higher ion transfer efficiency work together to significantly improve the rate performance of the battery, that is, the ability to charge and discharge at high currents.

[0034] (3) The poor interface contact of the prior art easily leads to side reactions at the interface, such as lithium dendrite growth and interface decomposition, which accelerate the battery capacity decay and shorten the cycle life. The tighter interface contact of the present invention can reduce the occurrence of interface side reactions and improve the stability of the interface. In addition, some ionic liquids can also form a stable interface layer with sulfide electrolytes or electrode materials, further inhibiting side reactions and improving the cycle life of the battery.

[0035] (4) Although all-solid-state batteries are safer than lithium-ion batteries using liquid electrolytes, interface problems may still lead to safety hazards such as local overheating. The present invention can reduce heat generation during battery operation by improving interface contact and reducing interface impedance, thereby indirectly improving battery safety.

[0036] (5) Traditional interface modification methods usually require complex preparation processes and specific equipment. The use of the ionic liquid of the present invention is relatively simple and flexible, and can be introduced into the interface by coating, mixing, infiltration and other methods. Suitable ionic liquids can be selected according to different electrode and electrolyte materials to achieve more effective interface modification. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a cycle performance diagram of the modified sulfide electrolyte applied to all-solid-state lithium metal in Example 1; Figure 2 This is a diagram of the coulombic efficiency of the modified sulfide electrolyte applied to an all-solid-state lithium metal battery in Example 1; Figure 3 This is a comparison chart of the cycle performance of the all-solid-state lithium metal battery of Example 1 of the present invention and the control group; Figure 4 This is a schematic diagram of electrowetting of the present invention. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] Example 1 The present embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The sulfide electrolyte used in the present embodiment is Li6PS5Cl, and the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF).

[0040] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1. Prepare materials: Sulfide solid electrolyte sheet: Li6PS5Cl powder (purchased from Yili Technology, particle size 1-8μm) was prepared into a sheet with a diameter of 10mm and a thickness of 100μm by cold pressing (cold pressing pressure of 400MPa, holding pressure for 30 minutes). Ensure that the surface of the sheet is flat and smooth without obvious cracks or holes. Before use, the sheet was dried overnight in an Ar gas glove box to remove adsorbed moisture.

[0041] Electrode sheet: This embodiment prepares a modified electrolyte, so only an electrode sheet for applying a DC signal is used here, such as a stainless steel sheet or copper sheet with a diameter of 10 mm. If the battery is assembled later, NCM811 can be used for the positive electrode and lithium metal can be used for the negative electrode.

[0042] Ionic liquid: 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) (purchased from Sigma-Aldrich) was used with a purity of ≥99%.

[0043] Solvent: Use anhydrous acetonitrile (e.g., purchased from Sigma-Aldrich) with a water content of <50 ppm.

[0044] Glove box: Ar gas atmosphere, water and oxygen content <1ppm.

[0045] Spin coater: Spin coating equipment with controllable speed and time.

[0046] Micro-injector: used to accurately take ionic liquid solutions.

[0047] S2. Ionic liquid coating: Dilution: Since BMIMPF has a high viscosity at room temperature (about 100 mPa·s), dilution is required to obtain a uniform film. Weigh 0.01g BMIMPF, add it to 0.99g acetonitrile, stir thoroughly until completely dissolved, and dissolve BMIMPF in anhydrous acetonitrile at a concentration of 1wt% to prepare an ionic liquid solution (viscosity 0.4 mPa·s). The preparation process is carried out in a glove box to prevent the ionic liquid from absorbing moisture.

[0048] Spin coating: Use a microinjector to take 50 μL of the prepared BMIMPF solution and drop it on the center of the sulfide electrolyte sheet. Fix the electrolyte sheet on the spin coater and spin coat at 500 rpm for 60 seconds, then continue to spin coat at 3000 rpm for 30 seconds. The final BMIMPF film thickness is about 50 nm. After spin coating, dry the modified electrolyte sheet in a glove box for 30 minutes to evaporate the residual acetonitrile.

[0049] S3. Assemble the parallel plate capacitor and apply a DC signal for 30 minutes: Assembly method: Figure 4 As shown, the ionic liquid-modified electrolyte sheet is placed on an electrode plate (stainless steel sheet).

[0050] Another identical electrode plate (stainless steel sheet) was placed in parallel above the electrolyte sheet, and the distance between the two plates was controlled using a 1 mm thick polytetrafluoroethylene (PTFE) insulating spacer and fixed with a clamp to form a parallel plate capacitor.

[0051] Use a DC power supply or signal generator connected to both ends of the capacitor to apply a 5V DC signal for 30 minutes. This step is intended to induce the ionic liquid to form a double electric layer at the electrolyte / electrode interface through the DC electric field, further improving the interfacial wettability.

[0052] Example 2 The present embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The sulfide electrolyte used in the present embodiment is Li6PS5Cl, and the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF).

[0053] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1. Prepare materials: Sulfide solid electrolyte sheet: Li6PS5Cl powder (purchased from Yili Technology, particle size 1-8μm) was prepared into a sheet with a diameter of 10mm and a thickness of 100μm by cold pressing (cold pressing pressure of 400MPa, holding pressure for 30 minutes). Ensure that the surface of the sheet is flat and smooth without obvious cracks or holes. Before use, the sheet was dried overnight in an Ar gas glove box to remove adsorbed moisture.

[0054] Electrode sheet: This embodiment prepares a modified electrolyte, so only an electrode sheet for applying a DC signal is used here, such as a stainless steel sheet or copper sheet with a diameter of 10 mm. If the battery is assembled later, NCM811 can be used for the positive electrode and lithium metal can be used for the negative electrode.

[0055] Ionic liquid: 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) (purchased from Sigma-Aldrich) was used with a purity of ≥99%.

[0056] Solvent: Anhydrous acetonitrile (purchased from Sigma-Aldrich) was used with a water content of <50 ppm.

[0057] Glove box: Ar gas atmosphere, water and oxygen content <1ppm.

[0058] Spin coater: Spin coating equipment with controllable speed and time.

[0059] Micro-injector: used to accurately take ionic liquid solutions.

[0060] S2. Ionic liquid coating: Dilution: Since BMIMPF has a high viscosity at room temperature (about 100 mPa·s), dilution is required to obtain a uniform film. Weigh 0.01g BMIMPF, add it to 0.99g acetonitrile, stir thoroughly until completely dissolved, and dissolve BMIMPF in anhydrous acetonitrile at a concentration of 1wt% to prepare an ionic liquid solution (viscosity 0.4 mPa·s). The preparation process is carried out in a glove box to prevent the ionic liquid from absorbing moisture.

[0061] Spin coating: Use a microinjector to take 50 μL of the prepared BMIMPF solution and drop it on the center of the sulfide electrolyte sheet. Fix the electrolyte sheet on the spin coater and spin coat at 500 rpm for 60 seconds, then continue to spin coat at 1000 rpm for 30 seconds. The final BMIMPF film thickness is about 10 μm. After spin coating, dry the modified electrolyte sheet in a glove box for 30 minutes to evaporate the residual acetonitrile.

[0062] S3. Assemble the parallel plate capacitor and apply a DC signal for 30 minutes: The ionic liquid-modified electrolyte sheet is placed on an electrode plate (stainless steel sheet).

[0063] Another identical electrode plate (stainless steel sheet) was placed in parallel above the electrolyte sheet, and the distance between the two plates was controlled using a 1 mm thick polytetrafluoroethylene (PTFE) insulating spacer and fixed with a clamp to form a parallel plate capacitor.

[0064] Use a DC power supply or signal generator connected to both ends of the capacitor to apply a 5V DC signal for 30 minutes. This step is intended to induce the ionic liquid to form a double electric layer at the electrolyte / electrode interface through the DC electric field, further improving the interfacial wettability.

[0065] Example 3 The present embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The sulfide electrolyte used in the present embodiment is Li6PS5Cl, and the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF).

[0066] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1. Prepare materials: Sulfide solid electrolyte sheet: Li6PS5Cl powder (purchased from Yili Technology) was prepared into a sheet with a diameter of 10 mm and a thickness of 100 μm by cold pressing (cold pressing pressure of 400 MPa, holding pressure for 30 minutes). Ensure that the surface of the sheet is flat and smooth without obvious cracks or holes. Before use, the sheet was dried overnight in an Ar gas glove box to remove adsorbed moisture.

[0067] Electrode sheet: This embodiment prepares a modified electrolyte, so only an electrode sheet for applying a DC signal is used here, such as a stainless steel sheet or copper sheet with a diameter of 10 mm. If the battery is assembled later, NCM811 can be used for the positive electrode and lithium metal can be used for the negative electrode.

[0068] Ionic liquid: 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) (purchased from Sigma-Aldrich) was used with a purity of ≥99%.

[0069] Solvent: Use anhydrous acetonitrile (e.g., purchased from Sigma-Aldrich) with a water content of <50 ppm.

[0070] Glove box: Ar gas atmosphere, water and oxygen content <1ppm.

[0071] Spin coater: Spin coating equipment with controllable speed and time.

[0072] Micro-injector: used to accurately take ionic liquid solutions.

[0073] S2. Ionic liquid coating: Dilution: Since BMIMPF has a high viscosity at room temperature (about 100 mPa·s), dilution is required to obtain a uniform film. Weigh 0.01g BMIMPF, add it to 0.99g acetonitrile, stir thoroughly until completely dissolved, and dissolve BMIMPF in anhydrous acetonitrile at a concentration of 1wt% to prepare an ionic liquid solution (viscosity 0.4mPa·s). The preparation process is carried out in a glove box to prevent the ionic liquid from absorbing moisture.

[0074] Spin coating: Use a microinjector to take 50 μL of the prepared BMIMPF solution and drop it on the center of the sulfide electrolyte sheet. Fix the electrolyte sheet on the spin coater and spin coat at 500 rpm for 60 seconds, then continue to spin coat at 2000 rpm for 30 seconds. The final BMIMPF film thickness is about 100 nm. After spin coating, dry the modified electrolyte sheet in a glove box for 30 minutes to evaporate the residual acetonitrile.

[0075] S3. Assemble the parallel plate capacitor and apply a DC signal for 30 minutes: The ionic liquid-modified electrolyte sheet is placed on an electrode plate (stainless steel sheet).

[0076] Another identical electrode plate (stainless steel sheet) was placed in parallel above the electrolyte sheet, and the distance between the two plates was controlled using a 1 mm thick polytetrafluoroethylene (PTFE) insulating spacer and fixed with a clamp to form a parallel plate capacitor.

[0077] Use a DC power supply or signal generator connected to both ends of the capacitor to apply a 5V DC signal for 30 minutes. This step is intended to induce the ionic liquid to form a double electric layer at the electrolyte / electrode interface through the DC electric field, further improving the interfacial wettability.

[0078] Example 4 The present embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The sulfide electrolyte used in the present embodiment is Li6PS5Cl, and the ionic liquid is 1-butyl-1-methylpyrrolidino hexafluorophosphate (BMPPF).

[0079] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1. Prepare materials: Sulfide solid electrolyte sheet: Li6PS5Cl powder (purchased from Yili Technology) was prepared into a sheet with a diameter of 10 mm and a thickness of 100 μm by cold pressing (cold pressing pressure of 400 MPa, holding pressure for 30 minutes). Ensure that the surface of the sheet is flat and smooth without obvious cracks or holes. Before use, the sheet was dried overnight in an Ar gas glove box to remove adsorbed moisture.

[0080] Electrode sheet: This embodiment prepares a modified electrolyte, so only an electrode sheet for applying a DC signal is used here, such as a stainless steel sheet or copper sheet with a diameter of 10 mm. If the battery is assembled later, NCM811 can be used for the positive electrode and lithium metal can be used for the negative electrode.

[0081] Ionic liquid: 1-Butyl-1-methylpyrrolidino hexafluorophosphate (BMPPF) (purchased from Sigma-Aldrich) was selected with a purity of ≥99%.

[0082] Solvent: Anhydrous acetonitrile (purchased from Sigma-Aldrich) was used with a water content of <50 ppm.

[0083] Glove box: Ar gas atmosphere, water and oxygen content <1ppm.

[0084] Spin coater: Spin coating equipment with controllable speed and time.

[0085] Micro-injector: used to accurately take ionic liquid solutions.

[0086] S2. Ionic liquid coating: Dilution: Since BMPPF has a high viscosity at room temperature (about 100 mPa·s), dilution is required to obtain a uniform film. Weigh 0.01g BMPPF, add it to 0.99g acetonitrile, stir thoroughly until completely dissolved, and dissolve BMPPF in anhydrous acetonitrile at a concentration of 1wt% to prepare an ionic liquid solution (viscosity 0.4mPa·s). The preparation process is carried out in a glove box to prevent the ionic liquid from absorbing moisture.

[0087] Spin coating: Use a microinjector to take 50 μL of the prepared BMPPF solution and drop it on the center of the sulfide electrolyte sheet. Fix the electrolyte sheet on the spin coater and spin coat at 500 rpm for 60 seconds, then continue to spin coat at 2000 rpm for 30 seconds. The final BMPPF film thickness is about 100 nm. After spin coating, dry the modified electrolyte sheet in a glove box for 30 minutes to evaporate the residual acetonitrile.

[0088] S3. Assemble the parallel plate capacitor and apply a DC signal for 30 minutes: The ionic liquid-modified electrolyte sheet is placed on an electrode plate (stainless steel sheet).

[0089] Another identical electrode plate (stainless steel sheet) was placed in parallel above the electrolyte sheet, and the distance between the two plates was controlled using a 1 mm thick polytetrafluoroethylene (PTFE) insulating spacer and fixed with a clamp to form a parallel plate capacitor.

[0090] Use a DC power supply or signal generator connected to both ends of the capacitor to apply a 5V DC signal for 30 minutes. This step is intended to induce the ionic liquid to form a double electric layer at the electrolyte / electrode interface through the DC electric field, further improving the interfacial wettability.

[0091] Example 5 This embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this embodiment and Example 1 is that in the part of applying a DC signal for 30 minutes in step S3, a DC power supply or a signal generator is connected to both ends of a capacitor, and applying a 5V DC signal for 30 minutes is converted into applying a 1V DC signal for 30 minutes.

[0092] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0093] Example 6 This embodiment provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this embodiment and Example 1 is that in the part of applying a DC signal for 30 minutes in step S3, a DC power supply or a signal generator is connected to both ends of a capacitor, and applying a 5V DC signal for 30 minutes is converted into applying a 10V DC signal for 30 minutes.

[0094] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0095] Comparative Example 1 This comparative example provides an unmodified electrolyte and a preparation method thereof. The sulfide electrolyte used in this comparative example is Li6PS5Cl.

[0096] Comparative Example 2 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that in the spin coating step in S2, the electrolyte sheet is fixed on the spin coater, spin coated at a speed of 500 rpm for 60 seconds, and then spin coated at a speed of 5000 rpm for 30 seconds. The thickness of the BMIMPF film finally obtained is about 40 nm.

[0097] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0098] Comparative Example 3 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that in the spin coating step in S2, the electrolyte sheet is fixed on the spin coater, spin coated at a speed of 500 rpm for 60 seconds, and then spin coated at a speed of 500 rpm for 30 seconds. The thickness of the BMIMPF film finally obtained is about 20 μm.

[0099] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0100] Comparative Example 4 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 3 is that the ionic liquid is replaced by 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) with 1-ethyl-3-methylimidazolium bistrifluoromethylsulfonimide (EMIMTFSI).

[0101] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 3.

[0102] Comparative Example 5 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 3 is that the ionic liquid is replaced by 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) with N-butylpyridinium bis(trifluoromethylsulfonyl)imide.

[0103] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 3.

[0104] Comparative Example 6 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 3 is that the obtained BMIMPF film is not subjected to electrowetting treatment.

[0105] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S2 are the same as in Example 3.

[0106] Comparative Example 7 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that in the part of applying a DC signal for 30 minutes in step S3, a DC power supply or a signal generator is connected to both ends of a capacitor, and applying a 5V DC signal for 30 minutes is converted into applying a 0.5V DC signal for 30 minutes.

[0107] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0108] Comparative Example 8 This comparative example provides an ionic liquid electrowetting modified electrolyte and a preparation method thereof. The difference between this comparative example and Example 1 is that in the part of applying a DC signal for 30 minutes in step S3, a DC power supply or a signal generator is connected to both ends of a capacitor, and applying a 5V DC signal for 30 minutes is converted into applying an 11V DC signal for 30 minutes.

[0109] The preparation method of the ionic liquid electrowetting modified electrolyte comprises the following steps: S1-S3 are the same as in Example 1.

[0110] Performance test case The products prepared in the above examples and comparative examples were assembled: in an inert gas glove box with a water and oxygen content of ≤0.01 ppm, the corresponding electrolyte was used as the electrolyte layer, and the positive electrode was a NCM811 loading of 10 mg cm per unit area. -2The electrode is a lithium metal anode layer, and the battery is assembled into a solid-state lithium metal battery. Finally, the battery is subjected to external pressure-free cyclic discharge, first with 0.1C charge and discharge for two cycles, and then with 0.5C for long cycle test. The first efficiency is tested, and the capacity retention rate is tested after 500 cycles. The results are shown in Table 1: Table 1 Cyclic performance test

[0111] According to Table 1, when 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF) and 1-butyl-1-methylpyrrolidine hexafluorophosphate (BMPPF) ionic liquid electrowetting modified electrolytes are added and the thickness is 50nm-10μm as electrolytes, higher first effect and capacity retention can be achieved, and the performance of the all-solid-state lithium metal life can be improved. Figure 1 It can be seen that Example 1 has excellent cycle ability and capacity retention; Figure 2 It can be seen that its excellent Coulomb efficiency; Figure 3 It can be seen that the cycle performance of the all-solid-state lithium metal battery is prepared.

[0112] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A sulfide solid electrolyte based on ionic liquid electrowetting modification, characterized in that: Prepared by a method comprising the following steps: S1. Prepare a sulfide electrolyte into an electrolyte sheet, and then coat an ionic liquid on the surface of the electrolyte sheet to form an ionic liquid film, thereby obtaining an electrolyte sheet containing an ionic liquid film; the ionic liquid is one or more of 1-butyl-3-methylimidazolium hexafluorophosphate and 1-butyl-1-methylpyrrolidium hexafluorophosphate; S2. Placing the electrolyte sheet containing the ionic liquid film between parallel electrode plates to assemble into a parallel plate capacitor, applying a DC signal for electrowetting treatment, and obtaining a sulfide solid electrolyte modified by ionic liquid electrowetting.

2. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 1, characterized in that: In step S1, the sulfide electrolyte includes Li6PS5Cl, Li3PS4, Li 10 GeP2S 12 , Li6PS5Br, Li6PS5I.

3. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 1, characterized in that: In step S1, the preparation process of the electrolyte sheet is a cold pressing process or a hot pressing process.

4. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 1, characterized in that: In step S1, the thickness of the formed ionic liquid film is 50 nm-20 μm.

5. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 1, characterized in that: In step S2, the voltage of the DC signal is 1-10V, and the time of the electrowetting treatment is 15-60 minutes.

6. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 1, characterized in that: In step S2, the parallel plate capacitor is assembled by placing an electrolyte sheet containing an ionic liquid film on a second electrode plate, the ionic liquid film is in contact with the second electrode plate, and then placing an insulating spacer on the electrolyte sheet. The first electrode plate is placed parallel to the insulating spacer, and finally a power supply or a signal generator is connected to the first and second electrode plates at both ends of the capacitor, and a DC signal is applied.

7. The sulfide solid electrolyte based on ionic liquid electrowetting modification according to claim 6, characterized in that: In step S2, when a DC signal is applied, the second electrode plate is connected to the negative electrode, and the first electrode plate is connected to the positive electrode.

8. Use of the sulfide solid electrolyte modified by ionic liquid electrowetting as claimed in claim 1 in an all-solid-state lithium metal secondary battery.

9. An all-solid-state lithium metal secondary battery, characterized in that: The invention comprises a negative electrode, a positive electrode and the sulfide solid electrolyte modified by ionic liquid electrowetting as claimed in claim 1.

10. The all-solid-state lithium metal secondary battery according to claim 9, characterized in that: The negative electrode comprises a lithium metal negative electrode or a metal lithium composite negative electrode; And / or, the positive electrode includes one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide.

Citation Information

Patent Citations

  • Preparation method of flexible hydrophobic dielectric film for electrowetting device

    CN110272559A

  • Thin solid electrolyte with high ionic conductivity

    CN116565303A

  • Liquid injection process of lithium ion battery and lithium ion battery

    CN118472570A

Cited By

  • Sulfide composite solid electrolyte and preparation method and application thereof

    CN121662924A

  • High-temperature-resistant all-solid-state lithium battery and preparation method thereof

    CN122659249A